Quantifying timeframes for transitioning the management of a fresh release of LNAPL petroleum from active recovery to natural source zone depletion: Evidence from intensive field investigation of a new diesel release - John L. Rayner; Mike J. Donn; Andrew King; Kaveh Sookhak Lari; Greg B. Davis (Water Research, 2026)

On environmental science computational labs - Kaveh Sookhak Lari; Greg B. Davis; John L. Rayner; Aaron W. Thornton; Aleks Reinhardt; S. Majid Hassanizadeh (Chemical Engineering Journal, 2026)

Quantifying timeframes for transitioning the management of a fresh release of LNAPL petroleum from active recovery to natural source zone depletion: Simulation of a new diesel release - Kaveh Sookhak Lari; Greg B. Davis; John L. Rayner; Mike J. Donn (Journal of Environmental Management, 2026)

In situ XANES study of PFAS impacted soils filled with aqueous and non-aqueous phases - Anand Kumar; Md Khairul Alam; Bin Qian; Mike J. Donn; Divina A. Navarro; John L. Rayner; Greg B. Davis; Bruce Cowie; Bobby Pejcic; Steve Fisher (Journal of Contaminant Hydrology, 2026)

Public support for food subsidy and tax scenarios to promote healthy and sustainable diets: Evidence from deliberative forums in two UK locations - Hannah Forde; Peter Scarborough; Lucy Yates; Jessica Renzella; Mark Sheehan; John Buckell; Alice O’Hagan; Sian Taylor; Jane Ward; Annie Connolly; Mike Rayner; Richard Smith; et al. (Food Policy, 2025)

Assessment of sealants for the mitigation of PFAS leaching from contaminated concrete - Grant B. Douglas; Prashant Srivastava; Rai Kookana; Mike Williams; Greg B. Davis; John Rayner; Canh Tien Trinh Nguyen; Sonia Mayakaduwage; Jason K. Kirby (Journal of Hazardous Materials, 2025)

Intercomparison of in-well, depth profile and online soil gas measurements for estimating petroleum natural source zone depletion rates: Will in-well gas samples suffice? - Greg B. Davis; John L. Rayner; Mike J. Donn; Trevor P. Bastow; Andrew Furness; Yasuko Geste; Andrew King (Journal of Hazardous Materials, 2025)

Collaborating with Marine Birds to Monitor the Physical Environment Within Coastal Marine Protected Areas - Rachael Orben; Adam Peck-Richardson; Alexa Piggott; James Lerczak; Greg Wilson; Jessica Garwood; Xiaohui Liu; Sabir Muzaffar; Alexa Foster; Humood Naser; Mohamed AlMusallami; Tycho Anker-Nilssen; et al. (Oceanography, 2025)
Animal telemetry is maturing into a viable method for observing the ocean as it can be used to monitor both environmental conditions and biological metrics along the movement trajectories of marine animals. As part of the Cormorant Oceanography Project, we have augmented a biologging tag with an external fast response temperature sensor to collect ocean temperature profiles from the backs of foraging marine birds. Cormorants dive between 50 and 250+ times a day to forage for prey so they can provide hard-to-match temporal and spatial coverage of coastal ocean conditions within their foraging areas. We process tag measurements to obtain fundamental oceanographic data (e.g., temperature profiles, bottom soundings, surface current measurements). Together, we have tracked 17 marine bird species (including two Spheniscus penguins spp. and a sea duck), originating from 17 countries and foraging along the edges of all major oceans. Tagged birds’ distribution included 191 MPAs in 26 countries, offering a unique ocean monitoring method to complement more widely used methods.

Natural Source Zone Depletion of crude oil, gasoline, diesel and aviation gasoline petroleum in the same soil/aquifer system – An intensive intercomparison field study and simulation - John L. Rayner; Mike J. Donn; Greg B. Davis; Trevor P. Bastow; Kaveh Sookhak Lari; Colin D. Johnston; Andrew King; Andrew Furness (Science of The Total Environment, 2024)

Advective and diffusive gas phase transport in vadose zones: Importance for defining vapour risks and natural source zone depletion of petroleum hydrocarbons - Kaveh Sookhak Lari; Greg B. Davis; John L. Rayner; Trevor P. Bastow (Water Research, 2024)

On quantifying global carbon emission from oil contaminated lands over centuries - Kaveh Sookhak Lari; Greg B. Davis; Trevor Bastow; John L. Rayner (Science of The Total Environment, 2024)

Advancing “Autonomous” sensing and prediction of the subsurface environment: a review and exploration of the challenges for soil and groundwater contamination - Greg B. Davis; John L. Rayner; Michael J. Donn (Environmental Science and Pollution Research, 2023)
Can we hope for autonomous (self-contained in situ) sensing of subsurface soil and groundwater pollutants to satisfy relevant regulatory criteria? Global advances in sensors, communications, digital technologies, and computational capacity offer this potential. Here we review past efforts to advance subsurface investigation techniques and technologies, and computational efforts to create a digital twin (representation) of subsurface processes. In the context of the potential to link measurement and sensing to a digital twin computation platform, we outline five criteria that might make it possible. Significant advances in sensors based on passive measurement devices are proposed. As an example of what might be achievable, using the five criteria, we describe the deployment of online real-time sensors and simulations for a case study of a petroleum site where natural source zone depletion (NSZD) is underway as a potential biodegradation management option, and where a high-quality conceptual site model is available. Multiple sensors targeting parameters (major gases and temperature influenced by soil moisture) relevant to the subsurface NSZD biodegradation processes are shown to offer the potential to map subsurface processes spatially and temporally and provide continuous estimates of degradation rates for management decisions, constrained by a computational platform of the key processes. Current limitations and gaps in technologies and knowledge are highlighted specific to the case study. More generally, additional key advances required to achieve autonomous sensing of subsurface soil and groundwater pollutants are outlined.

Designing and managing biodiverse streetscapes: key lessons from the City of Melbourne - Hui-Anne Tan; Lee Harrison; Jeff Nelson; Maggie Lokic; John P. Rayner; Caragh G. Threlfall; Jessica Baumann; Adrian Marshall; Mark Callow; Jessica Peeler; Rebecca Korossy-Horwood; Chris Nicholson; et al. (Urban Ecosystems, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Ocean Integration: The Needs and Challenges of Effective Coordination Within the Ocean Observing System - Adèle Révelard; Joaquín Tintoré; Jacques Verron; Pierre Bahurel; John A. Barth; Mathieu Belbéoch; Jérôme Benveniste; Pascal Bonnefond; Eric P. Chassignet; Sophie Cravatte; Fraser Davidson; Brad deYoung; et al. (Frontiers in Marine Science, 2022)
Understanding and sustainably managing complex environments such as marine ecosystems benefits from an integrated approach to ensure that information about all relevant components and their interactions at multiple and nested spatiotemporal scales are considered. This information is based on a wide range of ocean observations using different systems and approaches. An integrated approach thus requires effective collaboration between areas of expertise in order to improve coordination at each step of the ocean observing value chain, from the design and deployment of multi-platform observations to their analysis and the delivery of products, sometimes through data assimilation in numerical models. Despite significant advances over the last two decades in more cooperation across the ocean observing activities, this integrated approach has not yet been fully realized. The ocean observing system still suffers from organizational silos due to independent and often disconnected initiatives, the strong and sometimes destructive competition across disciplines and among scientists, and the absence of a well-established overall governance framework. Here, we address the need for enhanced organizational integration among all the actors of ocean observing, focusing on the occidental systems. We advocate for a major evolution in the way we collaborate, calling for transformative scientific, cultural, behavioral, and management changes. This is timely because we now have the scientific and technical capabilities as well as urgent societal and political drivers. The ambition of the United Nations Decade of Ocean Science for Sustainable Development (2021–2030) and the various efforts to grow a sustainable ocean economy and effective ocean protection efforts all require a more integrated approach to ocean observing. After analyzing the barriers that currently prevent this full integration within the occidental systems, we suggest nine approaches for breaking down the silos and promoting better coordination and sharing. These recommendations are related to the organizational framework, the ocean science culture, the system of recognition and rewards, the data management system, the ocean governance structure, and the ocean observing drivers and funding. These reflections are intended to provide food for thought for further dialogue between all parties involved and trigger concrete actions to foster a real transformational change in ocean observing.

Pending recovery in the strength of the meridional overturning circulation at 26° N - Ben I. Moat; David A. Smeed; Eleanor Frajka-Williams; Damien G. Desbruyères; Claudie Beaulieu; William E. Johns; Darren Rayner; Alejandra Sanchez-Franks; Molly O. Baringer; Denis Volkov; Laura C. Jackson; Harry L. Bryden (Ocean Science, 2020)
The strength of the Atlantic meridional overturning circulation (AMOC) at 26∘ N has now been continuously measured by the RAPID array over the period April 2004–September 2018. This record provides unique insight into the variability of the large-scale ocean circulation, previously only measured by sporadic snapshots of basin-wide transport from hydrographic sections. The continuous measurements have unveiled striking variability on timescales of days to a decade, driven largely by wind forcing, contrasting with previous expectations about a slowly varying buoyancy-forced large-scale ocean circulation. However, these measurements were primarily observed during a warm state of the Atlantic multidecadal variability (AMV) which has been steadily declining since a peak in 2008–2010. In 2013–2015, a period of strong buoyancy forcing by the atmosphere drove intense water-mass transformation in the subpolar North Atlantic and provides a unique opportunity to investigate the response of the large-scale ocean circulation to buoyancy forcing. Modelling studies suggest that the AMOC in the subtropics responds to such events with an increase in overturning transport, after a lag of 3–9 years. At 45∘ N, observations suggest that the AMOC may already be increasing. Examining 26∘ N, we find that the AMOC is no longer weakening, though the recent transport is not above the long-term mean. Extending the record backwards in time at 26∘ N with ocean reanalysis from GloSea5, the transport fluctuations at 26∘ N are consistent with a 0- to 2-year lag from those at 45∘ N, albeit with lower magnitude. Given the short span of time and anticipated delays in the signal from the subpolar to subtropical gyres, it is not yet possible to determine whether the subtropical AMOC strength is recovering nor how the AMOC at 26∘ N responds to intense buoyancy forcing.

Observing Requirements for Long-Term Climate Records at the Ocean Surface - Elizabeth C. Kent; Nick A. Rayner; David I. Berry; Ryan Eastman; Vika G. Grigorieva; Boyin Huang; John J. Kennedy; Shawn R. Smith; Kate M. Willett (Frontiers in Marine Science, 2019)

Compensation between meridional flow components of the Atlantic MOC at 26° N - E. Frajka-Williams; C. S. Meinen; W. E. Johns; D. A. Smeed; A. Duchez; A. J. Lawrence; D. A. Cuthbertson; G. D. McCarthy; H. L. Bryden; M. O. Baringer; B. I. Moat; D. Rayner (Ocean Science, 2016)
From ten years of observations of the Atlantic meridional overturning circulation (MOC) at 26° N (2004–2014), we revisit the question of flow compensation between components of the circulation. Contrasting with early results from the observations, transport variations of the Florida Current (FC) and upper mid-ocean (UMO) transports (top 1000 m east of the Bahamas) are now found to compensate on sub-annual timescales. The observed compensation between the FC and UMO transports is associated with horizontal circulation and means that this part of the correlated variability does not project onto the MOC. A deep baroclinic response to wind-forcing (Ekman transport) is also found in the lower North Atlantic Deep Water (LNADW; 3000–5000 m) transport. In contrast, co-variability between Ekman and the LNADW transports does contribute to overturning. On longer timescales, the southward UMO transport has continued to strengthen, resulting in a continued decline of the MOC. Most of this interannual variability of the MOC can be traced to changes in isopycnal displacements on the western boundary, within the top 1000 m and below 2000 m. Substantial trends are observed in isopycnal displacements in the deep ocean, underscoring the importance of deep boundary measurements to capture the variability of the Atlantic MOC.

Observed decline of the Atlantic meridional overturning circulation 2004–2012 - D. A. Smeed; G. D. McCarthy; S. A. Cunningham; E. Frajka-Williams; D. Rayner; W. E. Johns; C. S. Meinen; M. O. Baringer; B. I. Moat; A. Duchez; H. L. Bryden (Ocean Science, 2014)
The Atlantic meridional overturning circulation (AMOC) has been observed continuously at 26° N since April 2004. The AMOC and its component parts are monitored by combining a transatlantic array of moored instruments with submarine-cable-based measurements of the Gulf Stream and satellite derived Ekman transport. The time series has recently been extended to October 2012 and the results show a downward trend since 2004. From April 2008 to March 2012, the AMOC was an average of 2.7 Sv (1 Sv = 106 m3 s−1) weaker than in the first four years of observation (95% confidence that the reduction is 0.3 Sv or more). Ekman transport reduced by about 0.2 Sv and the Gulf Stream by 0.5 Sv but most of the change (2.0 Sv) is due to the mid-ocean geostrophic flow. The change of the mid-ocean geostrophic flow represents a strengthening of the southward flow above the thermocline. The increased southward flow of warm waters is balanced by a decrease in the southward flow of lower North Atlantic deep water below 3000 m. The transport of lower North Atlantic deep water slowed by 7% per year (95% confidence that the rate of slowing is greater than 2.5% per year).

THE GODAE HIGH-RESOLUTION SEA SURFACE TEMPERATURE PILOT PROJECT - Craig Donlon; Kenneth Casey; Ian Robinson; Chelle Gentemann; Richard Reynolds; Ian Barton; Olivier Arino; John Stark; Nick Rayner; Pierre LeBorgne; David Poulter; Jorge Vazquez-Cuervo; et al. (Oceanography, 2009)

Oxidant Stress and Damage in Post-Ischemic Mouse Hearts: Effects of Adenosine - Benjamin Hack; Paul K. Witting; Benjamin S. Rayner; Roland Stocker; John P. Headrick (Molecular and Cellular Biochemistry, 2006)

Archean adakites from the Ashuanipi complex, eastern Superior Province, Canada: geochemistry, geochronology and tectonic significance - John A. Percival; Richard A. Stern; Nicole Rayner (Contributions to Mineralogy and Petrology, 2003)